The Performance Of Prostephanus Truncatus (Horn) on Different Sorghum Varieties Grown in Ghana - Mailafiya, D.M (University of Ghana, 2003)
Studies were carried out under ambient laboratory conditions of 32 °C ± 2 and 74 - 87 % r.h. to determine the suitability of sorghum grain as a substrate that would support both the feeding and breeding of Prostephanus truncatus (Horn). Three sorghum varieties (Framida, Mankaraga and Naga-White) and one maize variety (Obatanpa) grown in Ghana were used in the study. Three forms of the substrates: Whole grain, Coarsely-ground grain and Grain flour were used for bioassays. The Fj progeny and mean developmental periods recorded were used to determine susceptibility index for the different grain varieties. Mean weight of the insect progeny that emerged was also determined. Percentage damage due to P. truncatus infestation was assessed on the different grain varieties. Similarly, weight loss due to this beetle on the different grain varieties was determined using both the standard volume/weight method and the count and weigh method for comparison. The effects of commodity compaction in storage, as well as disturbance on damage and weight loss were also determined. Furthermore, physical properties of grain, such as size, density, 100-grain weight, endosperm texture and grain hardness were determined to asses their influence on grain infestation by P. truncatus. Insect preference for the different grain varieties was also assessed. The results of the investigations revealed that P. truncatus can both feed and breed on sorghum grains. The mean developmental period and the mean weight of P. truncatus, as well as the grain susceptibility index were significantly (P<0.05) different. Mean developmental periods recorded were: 36-37 days on the high-yielding sorghum varieties (Framida and Naga-White), 46 days on a local low yielding variety (Mankaraga) and 21 days on the maize variety. Mean insect weight assessed were: 2.98 3.02 mg on high-yielding sorghum varieties, 2.49 mg on a local low- yielding sorghum variety and 4.91mg on maize. The high-yielding sorghum varieties (Framida and Naga-White) were more susceptible to P. truncatus infestation than the local low-yielding variety (Mankaraga), with the susceptibility index between 7.06 7.14 and 2.28, respectively. Obatanpa maize grains were the most susceptible, showing the highest susceptibility index of 19.09. Damage, weight loss, frass and progeny production were significantly (P<0.05) different among the grain varieties; highest mean values were recorded on Obatanpa (maize variety), followed by Framida and Naga-White (high-yielding sorghum varieties) and the least mean values assessed were on Mankaraga (local low-yielding sorghum variety). The mean values of these factors also increased with storage duration. Greater levels of compaction in storage significantly (P<0.05) provided favourable conditions for P. truncatus to thrive. Grains left undisturbed in storage, showed significant (P<0.05) differences, giving higher mean damage and loss values than those disturbed. The study showed that grains disturbed at a later stage in storage experienced less damage and loss than those disturbed early in storage. Grain size (r = 0.968, P = 0.032), grain hardness (r = -0.989. P = 0.093) and endosperm texture (r = 1.000, P = 0.019) had some influence on grain infestation by P. truncatus. Large grains provided the beetle with more carrying capacity for its activities. Grains with soft pericarp and soft endosperm (grain hardness) offered low resistance to the boring and tunneling activities of these beetles. These results show that, with the spread of the Larger Grain Borer in the sorghum growing areas of West Africa, sorghum is at risk of infestation in storage. Appropriate control measures should therefore be applied to keep this pest in check.
Thesis (MPhil) -University of Ghana, 2003